Chinese Herbal Medicine for Reducing Chemotherapy-Associated Side-Effects in Breast Cancer Patients: A Systematic Review and Meta-Analysis - Li, Sha; So, Tsz-him; Tang, Guoyi; Tan, Hor-Yue; Wang, Ning; Ng, Bacon Fung Leung; Chan, Chris Kam Wa; Yu, Edwin Chau-Leung; Feng, Yibin (Frontiers in Oncology, 2020)
Background: Chemotherapy usually induces a variety of side-effects in cancer treatment as it cannot tell normal cells apart from cancer cells and kills both. Chinese herbal medicine (CHM) has been regarded as a potential effective intervention for relieving the side-effects of chemotherapy in breast cancer patients. Objective: This study aims to conduct a comprehensive systematic review and meta-analysis to evaluate the efficacy of CHM as adjuvant therapy for reducing the chemotherapy-induced side-effects in the treatment of breast cancer. Methods: Main electronic databases were searched up to May 2020 for Randomized Controlled Trials (RCTs) evaluating the effect of CHM on breast cancer patients with chemotherapy. The PRISMA statement was adopted in this study and meta-analyses were performed. Results: The included studies showed unsatisfied quality. Results based on available literature indicated that the adjunctive use of CHM with chemotherapy may reduce the chemotherapeutic agents-associated adverse events, including nausea and vomiting, diarrhea, alopecia, myelosuppression and impaired immune function. Conclusion: A confident conclusion could not be have due to the lack of large scale and high quality trials.